# Calculator search results

Formula
Solve the equation
$2 \left( 3-5n \right) = 36$
$n = - 3$
 Solve a solution to $n$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ n } \right ) = 36$
 Multiply each term in parentheses by $2$
$\color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) \color{#FF6800}{ n } = 36$
$\color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } + 2 \times \left ( - 5 \right ) n = 36$
 Multiply $2$ and $3$
$\color{#FF6800}{ 6 } + 2 \times \left ( - 5 \right ) n = 36$
$6 + \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) \color{#FF6800}{ n } = 36$
 Simplify the expression 
$6 \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ n } = 36$
$\color{#FF6800}{ 6 } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ n } = 36$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ n } \color{#FF6800}{ + } \color{#FF6800}{ 6 } = 36$
$- 10 n \color{#FF6800}{ + } \color{#FF6800}{ 6 } = 36$
 Move the constant to the right side and change the sign 
$- 10 n = 36 \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$- 10 n = \color{#FF6800}{ 36 } \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
 Subtract $6$ from $36$
$- 10 n = \color{#FF6800}{ 30 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ n } = \color{#FF6800}{ 30 }$
 Change the sign of both sides of the equation 
$10 n = - 30$
$\color{#FF6800}{ 10 } \color{#FF6800}{ n } = \color{#FF6800}{ - } \color{#FF6800}{ 30 }$
 Divide both sides by the same number 
$\color{#FF6800}{ n } = \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
Solution search results